Towards better communities manual and textual writing format on comprehensive shelter & land use plan formulation - Baguios, Erlinda G. (Housing and Urban Development Coordinating Council (HURDCC), 1993)
This manual is a guide for local government units, urban and regional planners and consultants. It provides guidelines and instructions on gathering the essential data required to present the socio-economic profile of a particular city and/or municipality and development need projections. It also provides instructions on the prototype textual writing format of plan elements and formulation of the zoning ordinance.